Discussion about the feasibility of the employment of natural language processing tools in the identification of binding decisions in judicial processes - Boeing, Daniel Henrique Arruda (2020)
This paper discusses the use of Natural Language Processing (NLP) tools on the identification of binding precedents themes in legal documents. Therefore, there are legal and technical explanations. From the legal standpoint, the paper examines the: (a)  Binding Precedents System instituted by the Brazilian Code of Civil Procedure from 2015; (b) the new legal mindset required to its adoption; and (c) how it aims to provide more celerity, isonomy and legal security to judgements. From the technical standpoint, NLP tools are presented in order to analyse the feasibility of their implementation on the identification of the convergence between the precedent and the document as a support to expert agents’ decision making. Finally, dynamics and results from LEIA Precedents are presented, a real-case project through which this strategy was successfully carried out.